(untitled) (Journal of Information Technologies in Education (ITE), 2025)
Relevance of the study lies in the rapid digitalization of the educational and scientific space, which requires new approaches to communicating scientific knowledge. Traditional text formats are losing effectiveness in conveying information to a broad audience, especially in an environment dominated by visual content. In this context, Wikimedia platforms—including Wikipedia, Wikimedia Commons, and Wikiversity—are viewed as essential components of the digital science infrastructure that bridge academic and public domains. Presenting scientific concepts through images, animation, video, and other interactive formats enhances comprehension of complex ideas and improves the quality of scientific and educational communication. This approach is particularly relevant in the era of globalized knowledge, when research outcomes must be accessible not only to experts but also to the general public. The aim of this article is to justify modern approaches to the audiovisual representation of scientific information on Wikimedia platforms. The study classifies existing types of science-oriented audiovisual content across Wikipedia, Wikimedia Commons, Wikiversity, and related platforms. It also defines the core principles of audiovisual representation of scientific knowledge online—clarity, accuracy, reliability, open dissemination of science, broad audience engagement, adherence to free licensing requirements, and respect for copyright. The article provides examples of effective use of audiovisual media to illustrate complex scientific concepts in various disciplines, helping audiences grasp abstract ideas, understand intricate processes, and sustain interest in scientific topics. To ensure the quality of audiovisual scientific content on Wikimedia platforms, the authors propose the following recommendations: engaging researchers, educators, and Wikimedia editors in creating and distributing freely licensed audiovisual materials that visualize research findings and explain complex concepts; ensuring scientific validity and accuracy of created content; and improving accessibility—for example, by adding subtitles to videos or alternative text descriptions to images.